2017
DOI: 10.2174/1389203717666160813162629
|View full text |Cite
|
Sign up to set email alerts
|

Functions of Antimicrobial Peptides in Vertebrates

Abstract: AMPs are multifunctional peptides that participate in immune responses, wound healing, angiogenesis, toxin neutralization, iron metabolism, male reproduction, among other functions. However, AMPs may also contribute to excessive inflammation and tumorigenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 0 publications
2
32
0
1
Order By: Relevance
“…The β‐defensins are a large family of peptides that exhibit a range of different functions besides antimicrobial activity. For example, a rat epididymis‐specific β‐defensin, Bin1b, can bind to the sperm head and initiate sperm motility (Zhou et al, ), whereas the human β‐defensin 1 was shown to interact with CCR6 to promote sperm motility in the reproductive tract (Diao et al, ), Moreover, β‐defensin (DefbD9) in mice and bovine β‐defensin (called SPAG‐11) are both correlated with sperm motility (Avila, ). In the present work, β‐defensin 129 in seminal extracellular vesicles was shown to be negatively correlated with sperm motility; it has been reported that a common mutation in β‐defensin 129 causes impaired sperm penetration through the cervical mucus and not reduced progressive motility (Tollner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The β‐defensins are a large family of peptides that exhibit a range of different functions besides antimicrobial activity. For example, a rat epididymis‐specific β‐defensin, Bin1b, can bind to the sperm head and initiate sperm motility (Zhou et al, ), whereas the human β‐defensin 1 was shown to interact with CCR6 to promote sperm motility in the reproductive tract (Diao et al, ), Moreover, β‐defensin (DefbD9) in mice and bovine β‐defensin (called SPAG‐11) are both correlated with sperm motility (Avila, ). In the present work, β‐defensin 129 in seminal extracellular vesicles was shown to be negatively correlated with sperm motility; it has been reported that a common mutation in β‐defensin 129 causes impaired sperm penetration through the cervical mucus and not reduced progressive motility (Tollner et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The defensin family of genes expressed maternally and by the fetus probably combat bacteria ascending from the vagina, but possibly from other sources. Several defensins are known to be produced by fetal membranes including DEFB1 (Avila ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, AMPs are noted as key players in immune regulation . Studies have documented AMPs as not only involved in the initiation and progression of periodontal diseases, but also as implicated in the immune‐inflammatory responses that characterize the well‐established risk factors of periodontal diseases .…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, AMPs are noted as key players in immune regulation. 8,9 Studies have documented AMPs as not only involved in the initiation and progression of periodontal diseases, but also as implicated in the immune-inflammatory responses that characterize the well-established risk factors of periodontal diseases. [10][11][12][13][14][15] However, it remains unclear how and if AMPs form a common biological pathway or mechanistic link that underlies the relationship between periodontal diseases and its risk factors.…”
mentioning
confidence: 99%